Hubungan Postur Kerja dengan Keluhan Nyeri Otot pada Pekerja Industri Tahu di Wonogiri - Wangsit Restu Adi Guritno; Sri Darnoto (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Muscle pain complaints, characterized by soreness, heaviness, and stiffness in muscles that can be felt from the neck to the feet, often arise from prolonged periods of inappropriate work postures and extended working hours. This quantitative cross-sectional study aimed to analyze the relationship between work posture and muscle pain complaints among tofu industry workers in Wonogiri. The sample included the entire worker population, totaling 48 tofu industry workers in Wonogiri District, Wonogiri Regency. The research instruments used were the Ovako Work Posture Analysis System (OWAS) sheet for measuring work posture variables and the Nordic Body Map (NBM) sheet for muscle pain complaint variables. Data analysis was performed using the Spearman Rank Correlation test. Univariate analysis revealed that 43.8% of respondents had high-risk work postures, and 52.1% experienced moderate levels of muscle pain complaints. Bivariate analysis indicated a robust and significant positive correlation between work posture and muscle pain complaints (Spearman Rank correlation coefficient = 0.839; p-value = 0.000). This study demonstrated a highly significant correlation between work posture and complaints of muscle pain among tofu industry workers in Wonogiri. The study suggests further interventions, necessitating control measures, to reduce the high percentage of muscle pain complaints among these workers.